Sufism as a Generation (Z) Solution: A Review of Hamka’s Thoughts From a Multidimensional Context - Nasor, Moch. Azizi Saifun (Proceedings of International Conference on Muslim Society and Thought, 2024)
Tasawwuf, as a dimension within Islam that is often overlooked, emerges as a relevant solution for Generation Z in facing the complexities of the modern world. In Hamka’s thought, tasawwuf is seen as a multidimensional approach that offers a way out of the moral and ethical value crises rampant in contemporary society. This research aims to explore the contribution of tasawwuf in addressing the challenges of our times. A qualitative research method is used with a descriptive-analytical approach. The main findings indicate that tasawwuf teachings provide a foundation for creating harmony in human life. Essentially, tasawwuf aims to guide individuals towards a deeper closeness with God, which in turn shapes a more ethical and responsible society. In the context of a constantly changing modern society, tasawwuf plays a key role as a controller for humans against the currents of modernization. By rooting itself in strong spiritual values, tasawuf is capable of guiding Generation Z towards moral perfection and maintaining the integrity of noble values in everyday life.